Dictionary of pharmacy - Jarald, E. Edwin; Jarald, Sheeja Edwin (New Delhi, 2010)
Dictionary Of Pharmacy, authored by E. Edwin Jarald and Sheeja Edwin Jarald, is a book that describes more than 4500 words. Some of the words are terms related to Pharmaceutics, Chemistry, Herbal Medicine, Biology, Plant Tissue Culture and Enzymes.
Keywords: PHARMACOPOEIA/FORMULARIES; GENERAL REFERENCE